Direction finding method for wideband signals base on consistent focusing - CHEN Hong-guang; YU Sheng-fa; SHEN Zhen-kang (Tongxin xuebao)
MTLS focusing method needs estimating direction of arrival firstly.Estimation bias in only few frequency bins could impair the entire USCM（universal spatial covariance matrix）estimation.Consistent MTLS focusing method was proposed based on the idea of AMI（array manifold interpolating）.Simulations show CMTLS focusing method not only improves the focusing performance,but also reduces the computational burden.